The persistent power of human rights : from commitment to compliance - Sikkink, Kathryn, 1955-; Risse, Thomas, 1955-; Ropp, Steve C. (Cambridge studies in international relations, 2013)
"The Power of Human Rights (published in 1999) was an innovative and influential contribution to the study of international human rights. At its centre was a 'spiral model' of human rights change which described the various socialisation processes through which international norms were internalised into the domestic practices of various authoritarian states during the Cold War years. The Persistent Power of Human Rights builds on these insights, extending its reach and analysis. It updates our understanding of the various casual mechanisms and conditions which produce behavioural compliance, and expands the range of rights-violating actors examined to include democratic and authoritarian Great Powers, corporations, guerilla groups and private actors. Using a unique blend of quantitative and qualitative research and theory, this book yields not only important new academic insights but also a host of useful lessons for policymakers and practitioners"--